Comparative Study of Specific Loss Power and Transverse Relaxivity of Spinel Ferrite Nanoensembles Coated With Chitosan and Polyethylene Glycol - Hoque, S. Manjura; Islam, M. Khairul; Hoq, Amitra; Haque, M. Manjurul; Maritim, Samuel; Coman, Daniel; Hyder, Fahmeed (Frontiers in Nanotechnology, 2021)
We synthesized spinel ferrite nanoensembles (MnFe2O4, CoFe2O4, and Fe3O4) using the chemical co-precipitation method and characterized their physical, chemical, and magnetic properties were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), physical properties measurement system (PPMS), Mössbauer spectroscopy, Fourier transform infrared spectroscopy (FTIR), dynamic light scattering (DLS) and Raman spectroscopy. Their relaxation properties and potential for hyperthermia therapy were determined using nuclear magnetic resonance (NMR) and cell viability assay, respectively. XRD and TEM data confirmed that the particle core sizes were 6-9 nm before coating while their sizes increased to 10-14 nm and 14-20 nm after coating with chitosan and polyethylene glycol (PEG), respectively. Mössbauer spectroscopy showed superparamagnetic behavior for MnFe2O4 nanoparticles and ferrimagnetic behavior for the CoFe2O4 and Fe3O4 nanoparticles. A detailed studies of MH loops of all three ferrites before and after coating showed surface functionalization by a large reduction of coercivity and anisotropy. The successful coating was further confirmed by the peak shifts in the FTIR spectra of the particles whereas Raman spectra of coated ferrites also displayed the characteristic absorption patterns and suppression of the ferrite peaks suggesting successful coating. The induced heating profile of the nanoparticles in stable suspension was tested with a radio frequency magnetic field of 76 mT and a frequency of 400 kHz. High mortality (>98%) of 9L gliosarcoma cancer cells by hyperthermia suggested that these nanoparticles could be used for cancer therapy. Transverse relaxivities (r2) determined by NMR for chitosan-coated MnFe2O4, CoFe2O4, and Fe3O4 nanoparticles were 297(±22), 353(±26), and 345 (±13), mM-1S-1, while for PEG-coated nanoparticles are 165(±22), 146(±14), and 159 (±07) mM-1S-1, respectively. Overall these spinel ferrite nanoensembles show great promise for cancer theranostics research applications.